2009
DOI: 10.1128/cvi.00282-08
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extracellular ATP on Bovine Lung Endothelial and Epithelial Cell Monolayer Morphologies, Apoptoses, and Permeabilities

Abstract: Pneumonia in cattle is an important disease both economically and in terms of animal welfare. Recent evidence in other species has shown ATP to be an important modulator of inflammation in the lung, where it is released by activated alveolar macrophages and damaged lung cells. Whether ATP serves a similar process during infection in the bovine lung is unknown. In the present study, we examined the effects of ATP treatment on the morphology, apoptosis, and permeability of bovine pulmonary epithelial (BPE) cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
1
13
0
2
Order By: Relevance
“…The continuous deactivation of these cells may trigger irreparable liver failure 4 . The observation was supported by the investigation which reported that hepatomegaly as well as hepatitis inflammation of the liver was obvious in patients chronically exposed to antipsychotic drugs 35 . Differential treatments with functional oil from black seed moderately prevented these abnormalities.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The continuous deactivation of these cells may trigger irreparable liver failure 4 . The observation was supported by the investigation which reported that hepatomegaly as well as hepatitis inflammation of the liver was obvious in patients chronically exposed to antipsychotic drugs 35 . Differential treatments with functional oil from black seed moderately prevented these abnormalities.…”
Section: Discussionsupporting
confidence: 68%
“…The central site of xenobiotic metabolism known as liver is at risk to injury 35 . Also, one of the adverse effects of antipsychotic drugs is hepatotoxicity 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with pulmonary tuberculosis had significantly higher adenosine deaminase activity in bronchoalveolar lavage fluid (Orphanidou et al, 1998) and in the sputum (Dimakou et al, 2009). ATP is a modulator of lung inflammation in pneumonia in cattle; it is released by activated macrophages and damaged cells (McClenahan et al, 2009). It was shown in this study that ATP caused striking morphological and permeability changes in bovine pulmonary epithelial cells and that both epithelial cells and pulmonary microvascular endothelial cells expressed mRNA for P2X7 receptors, with a P2X7 receptor antagonist reversing the changes in permeability induced by ATP.…”
Section: Airway Infectionsmentioning
confidence: 74%
“…Both low levels of NE and high extracellular concentrations of ATP exhibit activating effects on leukocytes (52, 53). In addition, high extracellular ATP concentrations induce rapid increases in monolayer permeability of pulmonary epithelial and endothelial cells, allowing increased transmigration of immune cells to an area of acute infection (52, 54). …”
Section: Discussionmentioning
confidence: 99%